Gender Preferences for Urologists: Women Prefer Female Urologists - Sun-Ouck, Kim; Kang, Taek Won; Kwon, Dongdeuk (Urology Journal, 2017)
Purpose: To investigate patients’ preferences for the gender of their urologist. Materials and Methods: Patients who visited a urologic center were asked to complete a self-administered questionnaire on the preferences for the gender of their urologist as well as on their age, education level and employment status. Results: Of 270 respondents, 144 subjects (53%) had a preference for the gender of their urologist, whereas 126 subjects (47%) had no preference. Among 154 female respondents, 56 (36.4%) patients had no preference; 96 (62.3%) patients had preferences for female urologists; and only 2 (1.3%) patient preferred male urologists. Among 116 male respondents, 70 (60.3%) patients had no preference; 30 (25.9%) patients had preferences for male urologists; and 16 (13.8%) preferred female urologists. Of patients that did express a preference, 87.5% (126/144) preferred the same gender urologist, with 65.2% (30/46) of male patients preferring male urologists and 97.9% (96/98) of female patients preferring female urologists (p < .001). However, age and education level were not correlated with gender preference. Conclusion: More than half the female participants had a preference for the same gender of urologist, whereas the majority of male participants expressed no preference for the gender of their urologist. Furthermore, gender preference was not correlated with age and education level.